Analisa Kinerja Sistem Air Bersih di Desa Ponelo Kecamatan Ponelo Kepulauan - Nurain Naha; Aryati Alitu; Apriyanto A. Pahrun (Transbahasa, 2025)
This research employs a quantitative approach, which includes assessing community satisfaction with clean water services and testing water quality based on the standards outlined in the Minister of Health Regulation No. 2 of 2023. The results indicate that community perception falls into the